PENERAPAN SISTEM PENILAIAN TRAUMA REVISED TRAUMA SCORE (RTS) UNTUK MENENTUKAN MORTALITAS PASIEN TRAUMA DI TRIAGE INSTALASI GAWAT DARURAT - didik saudin; Mukamad Rajin (Jurnal Kesehatan Hesti Wira Sakti, 2017)
ABSTRACTBackground : Trauma is a condition caused injury or injury, therefore Trauma is an event that is holistic, potentially disrupting activity for patients. The most practical assessment for value trauma to the emergency conditions and the simplest is the RTS, results of several studies indicate that the scale of this aid in the triage of trauma and predict mortality.Method : The method used in this study using a non-parametric correlation test (Chi-squre), which will prove that the judging of RTS has a relationship with a mortality rate as well as the prognosis and treatment.Result : Use RTS assessment indicates that there is a significant relationship between ratings RTS with mortality predictor in cases of trauma. RTS is very good so if used in the case of pre-hospital or emergency room triage services.Conclusion : RTS become one of the alternative assessment system in trauma cases. RTS help is effective against predictors of mortality, prognosis or treatment of trauma on trauma cases